Skincare Antijerawat: Formulasi Masker Gel Peel-Off Etil P-Metoksisinamat dari Kaempferia galanga L dengan Polivinill Alkohol sebagai Gelling Agent - Kusuma, Ika Maruya; Indrawati, Teti; Zulfah, Zulfah (Jurnal Ilmiah Medicamento, 2025)
Herbal medicines are increasingly used as antibacterial therapy due to their accessibility and affordability. Kaempferia galanga L. (kencur) rhizome contains ethyl p-methoxycinnamate (EPMS), an active compound with anti-acne properties. EPMS at 1.2% in cream formulations has shown antibacterial activity against Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus. However, creams are unsuitable for oily skin as they may worsen acne. Peel-off gels offer a better alternative because it is non-greasy, supports exfoliation, stimulates cell regeneration, minimizes pores, and helps cleanse and moisturize the skin. This study aimed to formulate a physically stable anti-acne peel-off gel containing EPMS using polyvinyl alcohol (PVA) at 10% and 12%. EPMS was isolated from kencur rhizome and incorporated into gel bases. Evaluations included organoleptic properties, viscosity, homogeneity, pH, drying time, spreadability, and accelerated stability at 27 ± 2 °C and 40 ± 2 °C for 21 days. Results showed that EPMS can be successfully formulated into peel-off gels with PVA 10% and 12%. The gels exhibited yellowish-white color, honey-like odor, homogeneity, pH 5.21–5.35, drying time 17–30 minutes, spreadability 55–68 mm, and viscosity 4,900–16,000 cPs. All formulations maintained physical stability under test conditions. This study provides a scientific basis for the development of natural-based cosmetic products that are safe, particularly for oily skin, and do not worsen acne conditions.